The birth of ODL in Malaysia: an investigation of students' perceptions / Che Nooryohana Zulkifli and Nur Afiqah Ab. Latif - Zulkifli, Che Nooryohana; Ab. Latif, Nur Afiqah (Universiti Teknologi MARA, Pulau Pinang, 2022)
The infectious Coronavirus (COVID-19) which originated from China, has quickly evolved into a worrying worldwide health hazard, prompting most countries to impose mobility restrictions as a preventative precaution. Many people, especially university students, have been affected by Malaysia's implementation of the Movement Control Order (MCO) in March 2020, as face-to-face (FTF) classroom learning is no longer allowed. The traditional learning process, i.e. FTF has been abruptly replaced by virtual learning, also known as Open Distance Learning (ODL), resulting in both barriers and opportunities. Instructors were free to experiment with numerous types of online learning systems due to this abrupt deployment of MCO, which has presented students with some challenging conundrums. As a result, this article investigates the perceptions and experiences of students at a public university in Malaysia dealing with online learning during this moment of global emergency. The data was gathered through video recordings based on an interview protocol. The findings depict that despite experiencing ODL for the first time, the students are optimistic about it as they managed to go through it with minimal stress. ODL has somehow become the new norm, and both instructors and students will continue to use it during this unprecedented COVID-19 endemic.